Mechanism of Action of Icariin in Bone Marrow Mesenchymal Stem Cells. (4th April 2019) - Yang, Aofei; Yu, Chaochao; Lu, Qilin; Li, Hao; Li, Zhanghua; He, Chengjian
Abstract : Osteoporosis, femoral head necrosis, and congenital bone defects are orthopedic disorders characterized by reduced bone generation and insufficient bone mass. Bone regenerative therapy primarily relies on the bone marrow mesenchymal stem cells (BMSCs) and their ability to differentiate osteogenically. Icariin (ICA) is the active ingredient of Herba epimedii, a common herb used in traditional Chinese medicine (TCM) formulations, and can effectively enhance BMSC proliferation and osteogenesis. However, the underlying mechanism of ICA action in BMSCs is not completely clear. In this review, we provide an overview of the studies on the role and mechanism of action of ICA in BMSCs, to provide greater insights into its potential clinical use in bone regeneration.